A Culture of Religious Moderation as a Means of Internalizing Character Values and Strengthening Harmony among Elementary School Students - Shawmi, Ayu Nur; Rizky, Muhammad; Dewi, Windy Anisa; Juliana, Siti Arbaina; Akbar, Muhammad; Zahdi (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to describe the forms of implementation of a culture of religious moderation at Kartika II-5 Elementary School in Bandar Lampung and analyze its role in the process of internalizing students' character values. The research approach uses a descriptive qualitative method with data collection techniques in the form of participatory observation, interviews, and documentation involving the principal, teachers, and 13 students. The sampling technique is purposive sampling. Data analysis uses the Miles and Huberman model, namely data reduction, data presentation, and conclusion drawing. The techniques used to validate the data are source and technique triangulation. The results of the study indicate that a culture of religious moderation is integrated through several main indicators, namely national commitment, tolerance, anti-violence, and preservation of local culture. These four indicators are realized in intracurricular, co-curricular, and extracurricular activities through the habituation of religious attitudes, nationalism, mutual cooperation, independence, and integrity of students. This implementation has a positive influence on the formation of student character that is tolerant, has an attitude of respect for differences, and upholds unity. However, challenges arise from the influence of digital technology, requiring ongoing monitoring and strengthening of character literacy. This research confirms that a school culture based on religious moderation plays a strategic role in strengthening harmony and harmony in primary education.